Septic shock in children — recognition and management at an early stage - Hermann, Blanka; Piątkowski, Michał; Mędrzycka-Dąbrowska, Wioletta; Gaworska-Krzemińska, Aleksandra; Basiński, Andrzej (Nursing Problems / Problemy Pielęgniarstwa, 2015)
Septic shock is one of the most common reasons for admissions to pediatric intensive care units. Despite enormous progress in medicine in recent decades, it remains one of the main causes of mortality among children and poses a challenge in everyday clinical practice. Due to the dynamic course of the disease, early diagnosis and prompt and appropriate treatment become crucial. The aim of this article is to summarize the current standards for the early recognition of septic shock in pediatric patients and the treatment in its initial phase.